Place attachment, risk perception, and preparedness in a population exposed to coastal hazards: a case study in Faro Beach, southern Portugal - Domingues, Rita (2021)
Living by the coast is a high-risk choice, but most people do it voluntarily. At Faro Beach, a heavily urbanized settlement located on a sandy barrier peninsula exposed to coastal hazards, houses and roads were destroyed due to storm action. However, residents feel safe living there and have no intentions of relocating. The development and implementation of coastal management plans and disaster risk reduction measures require the understanding of psychological drivers of residents’ risk perception and behaviours. Thus, the main goal of this study is to evaluate the relationships between place attachment, risk perception, and preparedness in Faro Beach. We hypothesized that place attachment and past experience with hazards would have a negative effect on risk perception, while risk perception would positively influence preparedness. We administered a self-report questionnaire to 131 residents, and analysed the data using partial least squares modelling. Results show that stronger place attachment is associated with lower risk perception, as residents tend to accept the risk as part of their environment. Experience contributed to higher risk perception in Faro Beach residents, most likely because residents have had direct and personal experience with hazards and are fully aware of the consequences. In addition, risk perception was negatively associated with preparedness; although residents’ risk perception is moderate, probably due to risk normalisation, they still make some preparations to deal with a potential disaster. This study is useful for the design and implementation of more sustainable coastal management plans, as it validates the relevance of affective variables in risk perception and preparedness.